Neutrosophic Fuzzification Mathematical Modelling: Based on Survey Responses - M. Kavitha; R. Irene Hepzibah (Utilitas Mathematica, 2025)
Fuzzy is capable of converting human ideas into numbers. As a result, the fundamental purpose of this research is to employ a unique formula to convert the human views gathered in the survey into Neutrosophic values. A unique method for turning the crisp replies from the survey's questions to Neutrosophic Fuzzy numbers. A unique MATLAB method of converting Crispy information into Neutrosophic Fuzzy information was also created. To calculate rank of EE Beneficiaries, the Neutrosophic Fuzzy Weighted Arithmetic Operator Score (NWAAOS) is employed. It also contradicts the Pythagorean Fuzzy Weighted Arithmetic Average Operator Score method. The method for analyzing and prioritizing EE beneficiaries According to the study's findings, the late boomers will benefit the most. The NWAAOS rank will be the same as the PWAAOS rank. However, the Score values differ between NWAAOS and PWAAOS. This paper provides a novel approach for evaluating investigate questionnaire responses against a Neutrosophic fuzzy setting. An innovative MATLAB approach to generating Neutrosophic fuzzy numbers using data gathered and the NWAAOS Ranking. This one-of-a-kind method of translating investigate responses to Neutrosophic fuzzy kind will be applied to any sort of questionnaire.